One year update following removal of high sugar sweetened beverages from a university campus. (13th November 2019) - Fitzpatrick, P; O'Connor, J; Doyle, G; Delaney, L; Lades, L; Lawlor, O; Mullins, B; Murrin, C
Abstract: : Healthy UCD is a health promotion initiative designed to create a sustainable healthy university campus. The aim of the study was to report on student and staff attitudes and provider attitudes to the removal and income from drinks one year following the removal of carbonated sugar sweetened beverages (HSSBs) on a large university campus, University College Dublin (UCD). In 2018 Healthy UCD, in partnership with the contracted beverage supplier, conducted a seven-week trial where all HSSBs were removed from the main campus and replaced with sugar-free or low-sugar alternatives. This was in advance of a levy on HSSBs to be introduced nationally. During the trial, drinks sales rose by 4%. Following the trial, a survey of students was conducted across the campus which provided the motivation to the University Management Team to approve removal of HSSBs on a permanent basis. Staff and student complaints were monitored over the following year. Drinks sales data was obtained from retail outlets for 2019 and compared to the same sales period for the previous year. Retail sales for drinks continued to grow despite removal of HSSBs, with 8% growth in the year following removal. A small number of complaints were documented. The most important was a query about those staff and students with diabetes mellitus who might need high sugar energy products and the removal of a particular HSSB which is sold in Ireland. This HSSB had not in fact previously been sold in UCD. The national advice regarding access to high sugar products in the case of hypoglycaemia from Diabetes Ireland was provided satisfactorily for all staff and students. Removal of HSSBs from a university campus is possible; advice must be provided to those who may feel negatively impacted by the change. Key messages: Removal of high sugar sweetened drinks from a university campus is possible; advice must be provided to those who may feel negatively impacted by the change. Sales can grow despite health-related changes of the food environment.